Supporting interest in a study domain: A longitudinal test of the interplay between interest, utility-value, and competence beliefs. (April 2019) - Fryer, Luke K.; Ainley, Mary
Abstract: The current study used a longitudinal design to model initial interest and utility-value as antecedents of developing interest and course proficiency. Using measures from four time points across one academic year and competency assessed at the beginning of the previous year, we examined direct and mediated contributions of utility-value, self-efficacy, and self-concept for the development of domain interest. Japanese tertiary students ( n  = 614; Female = 129) undertaking a compulsory year-long study of English as a foreign language participated. Students reported motivation (interest, utility-value and competence beliefs of self-efficacy and self-concept) for studying English as a foreign language. In addition, the design allowed detection of reciprocal effects: the forward effect of interest on competence beliefs and in turn the forward effects of competence beliefs on interest. Initial domain interest indicated direct and/or mediated effects for all constructs, while self-efficacy indicated a reciprocal relationship with domain interest. Profile analyses (LPA) identified 3 motivation profiles that were stable across two semesters. Testing a mover-stayer model (LPTA) indicated some movement between the low and medium intensity profiles of motivation. Highlights: Self-efficacy and interest presented a reciprocal relationship. Initial interest predicted future competency beliefs, utility-value and achievement. Competency beliefs were important signals for movement between subgroups.